2021
DOI: 10.14311/app.2021.30.0093
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the Presence of Microorganisms During Production of Plasterboard

Abstract: This article is focused on detection microorganisms appearing during production of gypsum plasterboards. The research is carried out within the project TAČR ZÉTA TJ02000235 Sádrokarton se zvýšenou odolností proti bilogické degradaci (Gypsum plasterboard with increased biodegradation resistance). This article shows first part of this issue what was detection of the most critical place of production, where is the highest risk of bacterial contamination and it open the area to find suitable modification of produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Among the modern failures of prefab residential housing that have occurred, the degradation of the exterior plaster surface of ETICS can be included, which is the biodeterioration of the ETICS panel I. Professional studies on this topic can be found mainly by authors from Central Europe [79][80][81].…”
Section: Literature Review and State Of Artmentioning
confidence: 99%
“…Among the modern failures of prefab residential housing that have occurred, the degradation of the exterior plaster surface of ETICS can be included, which is the biodeterioration of the ETICS panel I. Professional studies on this topic can be found mainly by authors from Central Europe [79][80][81].…”
Section: Literature Review and State Of Artmentioning
confidence: 99%